Cooling and dehumidification using vortex tube. (25th July 2017) - Kumar, Aditya; Vivekanand; Subudhi, Sudhakar
Highlights: The optimum non-dimensional temperature drops and RH are following cubic equations. Hot temperature drop increases, then decreases with mass fraction for insulated case. Hot temperature drop increases only with mass fraction for the non-insulated case. Cold temperature drop increases and then decreases with mass fraction for both cases. Isentropic efficiency attains a constant value for both cases after some pressure. Abstract: The Ranque-Hilsch vortex tube (RHVT) is a small interesting extraordinary mechanical device used as refrigeration machine. An experimental setup has been developed for the study of both temperature and relative humidity separation in vortex tube for the two important cases: (a) with insulation and (b) without insulation on vortex tube. Two influential configurations are examined: (1) variations of cold mass fraction (by varying the mass flow at hot outlet) at different pressures and (2) variations of inlet pressures when the hot outlet is fully opened. Over the whole pressure range covered, the cold end temperature drop increases with the cold mass fraction and then decreases for both non-insulated and insulated cases. However, hot end temperature drop increases for whole range of the cold mass fraction for the non-insulated case, whereas it increases to some optimum value, then decreases with the cold mass fraction for the insulated case. Over the range of pressure the relative humidity increases to some optimum value, and then decreases with the cold mass fraction for both non-insulated and insulated cases. The maximum optimum value of relative humidity is found 65% and 67% at 4 bar inlet pressure with and without insulation respectively. Moreover, the correlations for cold end temperature drop, hot end temperature drop, relative humidity and isentropic efficiency have been developed and explained in this paper for the better understanding of the inside behavior of the RHVT. The variation of optimum non-dimensional cold/hot temperature drop with the cold mass fraction at different pressures obeys approximately single cubic equation and also it is true for the case of non-dimensional relative humidity.